Fatty Acid Synthase Inhibition by Amentoflavone Suppresses HER2/neu (erbB2) Oncogene in SKBR3 Human Breast Cancer Cells. (5th July 2012) - Lee, Jin Sun; Sul, Ji Young; Park, Jun Beom; Lee, Myung Sun; Cha, Eun Young; Song, In Sang; Kim, Je Ryong; Chang, Eil Sung
Abstract : Fatty acid synthase (FASN) is a potential therapeutic target for treatment of cancer and obesity, and is highly elevated in 30% of HER2‐overexpressing breast cancers. Considerable interest has developed in searching for novel FASN inhibitors as therapeutic agents in treatment of HER2‐overexpressing breast cancers. Amentoflavone was found to be effective in suppressing FASN expression in HER2‐positive SKBR3 cells. Pharmacological inhibition of FASN by amentoflavone specifically down‐regulated HER2 protein and mRNA, and caused an up‐regulation of PEA3, a transcriptional repressor of HER2. In addition, pharmacological blockade of FASN by amentoflavone preferentially decreased cell viability and induced cell death in SKBR3 cells. Palmitate reduced the cytotoxic effect of amentoflavone, as the percentage of viable cells was increased after the addition of exogenous palmitate. Amentoflavone‐induced FASN inhibition inhibited the translocation of SREBP‐1 in SKBR3 cells. Amentoflavone inhibited phosphorylation of AKT, mTOR, and JNK. The use of pharmacological inhibitors revealed that the modulation of AKT, mTOR, and JNK phosphorylation required synergistic amentoflavone‐induced FASN inhibition and HER2 activation in SKBR3 cells. These results suggest that amentoflavone modulated FASN expression by regulation of HER2‐pathways, and induced cell death to enhance chemopreventive or chemotherapeutic activity in HER2‐positive breast cancers. Copyright © 2012 John Wiley & Sons, Ltd.